2013
DOI: 10.2485/jhtb.22.41
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Compression Force on Apoptosis in Human Periodontal Ligament Cells

Abstract: The effect of compression force on periodontal ligament (PDL) plays a critical role in orthodontic tooth movement. However, little is known about this effect on apoptosis and the underlying reactive mechanisms in PDL cells. This study focuses on the application of compression force associated with reactive oxygen species (ROS)-induced apoptosis in PDL cells. Following the application of orthodontic force to maxillary first molars, the molars were investigated using immunohistochemical analysis. The cell cycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Our results show that centrifugal force or PEG-induced cell fusion increases via oxidative stress by generating ROS. Likewise, exposure of PDL 昀椀broblasts to mechanical compression increases intracellular ROS production [26]. Our results support the idea that the oxidative stress in cultured cells, subjected to centrifugal force or PEG-induced fusion, triggers biochemical pathways leading to TRAP and bone resorption activities characteristic of osteoclasts.…”
Section: Discussionsupporting
confidence: 86%
“…Our results show that centrifugal force or PEG-induced cell fusion increases via oxidative stress by generating ROS. Likewise, exposure of PDL 昀椀broblasts to mechanical compression increases intracellular ROS production [26]. Our results support the idea that the oxidative stress in cultured cells, subjected to centrifugal force or PEG-induced fusion, triggers biochemical pathways leading to TRAP and bone resorption activities characteristic of osteoclasts.…”
Section: Discussionsupporting
confidence: 86%
“…These findings are consistent with previous in vivo and in vitro studies, which have demonstrated that osteocyte apoptosis occurs under the orthodontic compressive force (Hoshi et al, 2014; Sakai et al, 2009). Moreover, compression can trigger apoptosis in other periodontal tissue cells like cementoblasts, osteoblasts and periodontal ligament cells (PDLCs) (Funakoshi et al, 2013; Goga et al, 2006; Yamaguchi et al, 2018). Intriguingly, the minimum force that caused osteocyte apoptosis (0.125 kPa, equivalent to 1.275 g/cm 2 ) is relatively close to that of cementoblasts (2.0 g/cm 2 ) and PDLCs (1.0 g/cm 2 ), but much higher than that of osteoblasts (2.04 × 10 −4 N/cm 2 , nearly 0.01 g/cm 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The non‐physiological mechanical stimuli are known to promote apoptosis through the mitochondrial‐ or death‐receptor‐mediated signaling pathways in several periodontal cells (Funakoshi et al, 2013; Song et al, 2016; Yamaguchi et al, 2018). However, there have been few mechanistic studies on compressive force‐induced osteocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…High level of cementocytes/cementoblasts apoptosis is associated with adverse orthodontic root resorption and upregulation of caspase 3 and caspase 8 which were induced by heavy or optimum orthodontic force [22,23]. Extreme levels of reactive oxygen species were observed on the compression zone that subsequently resulted in cell cycle arrest and apoptosis of the cells involved in the zone [24]. Stretching force may also cause apoptosis.…”
Section: Impact Of Hypoxia On Cellsmentioning
confidence: 99%